Role of Ureteroscoy and Retrograde Studies of the Ureter in Diagnosis and Treatment of Ureteric Pathology (Global Journal of Medical Research, 2014)
Ureteroscopy is defined as upper urinary tract endoscopy performed most commonly with an endoscope passed through the urethra, bladder, and then directly into the upper urinary tract. Indications for ureteroscopy have broadened from diagnostic endoscopy to various minimally invasive therapies. Objectives: To evaluate the effectiveness of Ureteroscopy and retrograde studies in diagnosis and treatment different ureteric pathology. Materials and Methods: This is a prospective cross sectional hospital based study conducted in Khartoum Sudan, in IbnSina hospital, Omdurman Military base hospital ISH, OMBH and SUH in the period between Oct 2012-Sep 2012. It included all patients who underwent Ureteroscopy and retrograde studies Results: Most patients were males in the ages between 31-40 yrs old, Loin pain was the most common presenting symptom in 116(91.3%).
Keywords: ureteroscopy; retrograde studies lithotriptor; DJ stent